2021
DOI: 10.3332/ecancer.2021.1333
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and palliative care in COVID-19 and other challenging situations – highlights from the Uganda Cancer Institute – Palliative Care Association of Uganda 3rd Uganda Conference on Cancer and Palliative Care, 23–24 September 2021, held in Kampala, Uganda and virtually

Abstract: The 3rd Uganda Conference on Cancer and Palliative Care was held in September 2021 with the theme: cancer and palliative care in COVID-19 and other challenging situations. It was hosted by the Uganda Cancer Institute and the Palliative Care Association of Uganda (UCI-PCAU). The conference was held virtually, with a mix of pre-recorded sessions, plenary sessions being broadcast live on television (TV) by the Uganda Broadcasting Corporation TV, live speakers at the studio and others presenting in real time via Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The need for cancer and palliative care services is on the rise both globally, in East Africa and in Uganda. Since the 3rd Uganda Conference in 2021 [ 1 ] COVID restrictions on meetings have been lifted, thus this 4th Uganda Conference on Cancer and Palliative Care run jointly by the Uganda Cancer Institute (UCI) and the Palliative Care Association of Uganda (PCAU), in collaboration with the Ministry of Health (MoH), was held in-person at the Speke Resort, Munyonyo. Delegates had the opportunity to come together again after the pandemic and discuss issues around scaling up availability, accessibility, quality and equity in cancer and palliative care provision, applying lessons learnt throughout the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The need for cancer and palliative care services is on the rise both globally, in East Africa and in Uganda. Since the 3rd Uganda Conference in 2021 [ 1 ] COVID restrictions on meetings have been lifted, thus this 4th Uganda Conference on Cancer and Palliative Care run jointly by the Uganda Cancer Institute (UCI) and the Palliative Care Association of Uganda (PCAU), in collaboration with the Ministry of Health (MoH), was held in-person at the Speke Resort, Munyonyo. Delegates had the opportunity to come together again after the pandemic and discuss issues around scaling up availability, accessibility, quality and equity in cancer and palliative care provision, applying lessons learnt throughout the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…During the first day of the session, topics such as choosing wisely principles, pharmacology, radiotherapy, screening and detection, oncological surgery, precision medicine, pain therapy and oncology interventionism and clinical trials were touched upon. The second day of the conference was dedicated to breast cancer, addressing topics from the San Antonio Breast Cancer Symposium 2021, American Society of Radiotherapy Oncology (ASTRO) 2021 and topics of vital importance in breast cancer such as: surgery in breast cancer in advanced stages, treatment of breast cancer during pregnancy, treatment of male breast cancer, management of breast cancer with relapse only at the level of the central nervous system and neoadjuvant endocrine therapy, among others [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…6 Prior to COVID-19, many cancer facilities in LMICs were already strained; COVID-19 placed an unprecedented burden on these facilities. 7 In one study of oncology providers from 18 African countries, more than 75% of providers reported a decrease in patient volume, and one-third reported modifications of cancer treatment, resulting in treatment delays. 8 Cancer is increasingly diagnosed in Africa, with more than one million diagnoses annually.…”
mentioning
confidence: 99%